2010
DOI: 10.1002/jbmr.32
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin gene polymorphisms influence concentration of serum osteocalcin and enhance fracture identification

Abstract: Osteoporosis is a major health problem affecting more than 75 million people throughout Europe, the United States, and Japan. Epidemiologic studies have determined that both genetic and environmental factors contribute to the pathogenesis of osteoporosis. We have investigated the association between polymorphisms at the osteocalcin locus and variables linked to bone health. Osteocalcin provides a link between bone and energy metabolism, hence its potential importance as an osteoporosis candidate gene. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 51 publications
(75 reference statements)
0
14
1
Order By: Relevance
“…Deng et al [32] in 2002 reported that the h allele of the osteocalcin gene Hin dIII polymorphism was associated with higher hip BMD using traditional linkage or association approaches conducted in 630 Caucasians from 53 pedigrees. A study from Sweden included a total of 996 women, all aged 75 years, and revealed that the promoter polymorphism rs1800247 was significantly associated with serum total osteocalcin [22]. There are also studies that failed to demonstrate a correlation between rs1800247 and BMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deng et al [32] in 2002 reported that the h allele of the osteocalcin gene Hin dIII polymorphism was associated with higher hip BMD using traditional linkage or association approaches conducted in 630 Caucasians from 53 pedigrees. A study from Sweden included a total of 996 women, all aged 75 years, and revealed that the promoter polymorphism rs1800247 was significantly associated with serum total osteocalcin [22]. There are also studies that failed to demonstrate a correlation between rs1800247 and BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variations in and around osteocalcin locus have been associated with serum osteocalcin concentrations and fracture in Caucasian women [22]. Many studies have revealed associations of the osteocalcin gene with BMD in various ethnic populations [23,24,25,26,27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we analyse 'any incident fracture' which includes hip, distal radius, vertebra, shoulder, pelvis and proximal tibia. The majority of fractures recorded were attributable to low energy trauma [38]. Excluded were fractures of the face, hands and feet and fractures resulting from pathology and high energy trauma.…”
Section: Incident Fracturesmentioning
confidence: 99%
“…Osteocalcin, also known as bone γ-carboxyglutamate protein (Bglap), is the most abundant noncollagenous protein in bone and comprises ∼1% of total body protein (McGuigan et al, 2010). An osteocalcin-deficient mouse model displays increased cortical bone thickness and density, trabecular bone and bone strength (Ducy et al, 1996).…”
Section: Introductionmentioning
confidence: 99%